2007
DOI: 10.1016/j.eurpsy.2006.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and demography of transsexualism in Belgium

Abstract: While in Flanders and in Brussels the prevalence is comparable to that in other Western European countries, in Wallonia it is markedly lower. Transsexualism in Wallonia appears to be socially less acceptable: persons suffering from gender dysphoria in that part of Belgium encounter more problems accessing gender clinics and receiving treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
119
11
16

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(162 citation statements)
references
References 13 publications
(18 reference statements)
16
119
11
16
Order By: Relevance
“…This suggests that many gender incongruent persons are probably not attending a secondary care service or gender clinic. Some persons may be reluctant to seek health care and treatment due to financial restraints, shame, or fear of potential social exclusion, such as losing one's family, job, friends or partner (De Cuypere et al, 2007;Kuyper & Wijsen, 2014;Zucker & Lawrence, 2009) whereas others may simply not desire hormonal treatment, SRS, or change of official documents. Our knowledge concerning this broader spectrum of gender nonconformity is currently scant (Conron, Scott, Stowel, & Landers, 2012;Kuyper & Wijsen, 2014).…”
Section: F640)mentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that many gender incongruent persons are probably not attending a secondary care service or gender clinic. Some persons may be reluctant to seek health care and treatment due to financial restraints, shame, or fear of potential social exclusion, such as losing one's family, job, friends or partner (De Cuypere et al, 2007;Kuyper & Wijsen, 2014;Zucker & Lawrence, 2009) whereas others may simply not desire hormonal treatment, SRS, or change of official documents. Our knowledge concerning this broader spectrum of gender nonconformity is currently scant (Conron, Scott, Stowel, & Landers, 2012;Kuyper & Wijsen, 2014).…”
Section: F640)mentioning
confidence: 99%
“…For example, the Belgian prevalence was based on the number of SRSs performed in Belgium, and was estimated at 1: 12,900 for male-to-female and 1:33,800 for female-to-male transsexual persons (De Cuypere et al, 2007). These interpretations of gender dysphoria imply an important selection bias as only those who seek and/or have access to medical and/or surgical treatment are counted.…”
Section: F640)mentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of such surgeries are difficult to estimate, but one study in Europe found that since 1985, the prevalence of gender reassignment surgery is 1:12,900 for male-tofemale and 1:33,800 for female-to-male transsexuals. 10 A meta-analysis found the prevalence to be 1:11,900 to 1:45,000 for male-to-female individuals in Belgium. 10 The prevalence is thought to be comparable in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…10 A meta-analysis found the prevalence to be 1:11,900 to 1:45,000 for male-to-female individuals in Belgium. 10 The prevalence is thought to be comparable in the United States. Surgery is an endpoint of gender reassignment, and patients often choose only hormonal therapy rather than full surgery.…”
Section: Discussionmentioning
confidence: 99%